Do audit and accounting practices matter for greenfield FDI inflows? - Jovana Stojanović; Bojan Srbinoski; Ksenija Denčić-Mihajlov (Economic Themes, 2022)
The study examines how the strength of the application of audit and accounting standards, as a component of the institutional infrastructure, affects the greenfield FDI in the four countries of the former Socialist Federal Republic of Yugoslavia over a twelve-year period (2006-2017). Using standard panel data econometric techniques, we conclude that stronger application of audit and accounting standards has a positive impact on attracting greenfield FDI, and that the strength of the application seems to be more important in stable business conditions. Our results are relevant to policy makers, as they point to the need for constant improvement in the accounting and audit system, thus encouraging better transparency and lower transaction costs for investors.
Keywords: F21; F40; 40; 330; Greenfield foreign direct investments; audit and accounting standards; compliance; Western Balkan countries